Potensi Seduhan Daun Pepaya (Carica papaya L.) Kombinasi Madu Terhadap Intensitas Nyeri Haid (Dysmenorrhea) pada Wanita: Potential Infusion of Papaya Leaves (Carica papaya L.) combined with honey Against the Intensity Menstrual Pain (Dysmenorrhea) in Women - Pakendek Fefryani; Nur Masyithah Zamruddin; Niken Indriyanti (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Menstruation is a sign that a teenager has entered puberty. Menstruation can cause pain or cramping called dysmenorrhea. In this study, 1 papaya leaf (Carica papaya L.) was used combined with 30 ml of honey. The purpose of this study was to determine the effectiveness of steeping papaya leaves (Carica papaya L.) combined with honey on the intensity of menstrual pain in women. In this test, 2 groups were used, namely the positive test and control using the Quasi Experimental research method by looking at the potential of herbal preparations on the NRS (Numerical Rating Scale) scale sheet given before and after treatment. Based on the results of the study, it was found that the effectiveness of papaya leaf tea with a combination of honey before and after administration to reduce the intensity of pain felt in each subject was significant, namely 0.000 (p <0.05) from the two treatment groups, namely the test and positive control, the comparison of pain was obtained from the leaves. papaya combined with honey was better and more effective in reducing dysmenorrhea pain after NSAIDs with a test mean ratio of 11.70 and positive control 9.30.